IMF Staff papers : Volume 28 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1981)
This paper constructs a general-equilibrium model of an open economy and to develop a computational technique for deriving a market-clearing solution to the model. The model will allow for disaggregated commodities, taxes, and tariffs, so that the individual parameter changes that are often considered by a government may be examined. The model includes a government that is an active participant in the economy as a producer of public goods and that may influence the rate of savings by its actions. Private firms are assumed to have linear technologies in intermediate and final goods, but have the possibility for substitution among the scarce factors that enter their value added, and are assumed to maximize profits at given market prices subject to taxes on profits, defined as returns to capital. It is the normal procedure in work on general-equilibrium models to deal separately with the supply and demand sides of the economy in question, and to then construct excess demand functions.